Analisis SWOT Terhadap Layanan Kardiovaskular Eka Hospital Pekanbaru - Deny Deny; Machasin Machasin; Jahrizal Jahrizal (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2020)
This study aimed to determine strategy for business unit based on quantitative SWOT analysis. This study was conducted in Eka Hospital Pekanbaru with the subject of research was Cardiovascular Services of Eka Hospital Pekanbaru. This study uses a qualitative analysis with internal data (primary data) and external data (secondary data). Sample of this study are individuals in hospital management. Determination of strategic factors in internal and external factors, ranking and weighting of each factor in the IFAS table and in the EFAS table was done through a Group Group Discussion (FGD). X value is obtained from the difference of total multiplication rating and weight of all factors in strength factors minus total multiplication rating and weight of all factors in the weakness factors. X value is 0.69 (possitive). Y value is obtained from the difference of total multiplication rating and weight of all factors in the ofactors minus total multiplication rating and weight of all factors in the weakness factors. Y value is 0.30, also possitive. Projection of X and Y in the SWOT quadrant are in the first quadrant. It means that progressive strategy (growth oriented strategy) is the recommended strategy because Eka Hospital Pekanbaru has strengths and good opportunities. Functional strategies are formulated based on progressive strategy as the recommendations strategy for business unit.